ANALYSIS RESULTS OF DISTRIBUTION FUNCTIONS FOR PROBABILITY DENSITY ASSESSMENT OF ACCIDENT LOCATIONS IN THE VICINITY OF THE AIRPORT - Gosudarska, Inna (Proceedings of National Aviation University (archive), 2017)
This paper contains the results of processing and statistical analysis of accident location data from the period 1973-2013 involving different types of large and light aircraft. The distribution of accident site locations which occurred during various phases of flight near-airport is presented. The analysis results of distribution functions are shown to estimate the probability density of accident locations during departures and arrivals. It is defined that the Weibull distribution and Gamma distribution are the most plausibly corresponded to describe the probability density of the accident site locations along the longitudinal and lateral coordinates relative to the runway centerline. The statistical characteristics of accident locations have obtained which took place in the vicinity of airports during take-off and landing phases of flight.